Pengabdian Masyarakat Melalui Kunjungan Industri Internasional; Peningkatan Praktek Pembelajaran Manajemen dan Strategi Pengelolaan Usaha dalam Perspektif Global - Ni Kadek Suryani (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2025)
One form of implementation of the Tri Dharma of Higher Education is industrial visit activities for the application of science, including industrial visits at the international level. This industrial visit was conducted at JJ Ardon Transport, located in Goes City, Zeeland, The Netherlands. This article aims to analyze the benefits and impacts on the enrichment of management knowledge and corporate management strategies at the global level applied to the companies visited. The methods used include direct observation, in-depth interviews, and documentation of operational practices in the company. The results of the discussion show that management practices, implementation of business strategies and modern technology have been implemented by JJ Ardon Transport and can be a reference for the management of similar companies in Indonesia. This article also provides recommendations for the implementation of the results of the visit in the development of higher education curricula and strengthening international collaboration.